Legal Implications of Cyber Bullying Crimes : A Comparative Study - Farizt Sultanul Husni; Taufiq Taufiq; Fandi Rahmadi; Kautsar Ramadhan; Muhammad Arnif; Muhammad Hatta (International Journal of Law, Crime and Justice, 2025)
Cyber bullying or bullying carried out online or cyberspace has become a serious and worrying issue in today's digital era, with a wide impact on victims and perpetrators. This phenomenon not only causes psychological and social disturbances for victims, but also poses serious challenges in law enforcement. This study aims to analyze and compare the legal implications of cyber bullying in several jurisdictions, especially Indonesia, the United Kingdom, the United States, and South Korea. Through a normative juridical approach and comparative or comparative legal methods, this study analyzes the regulatory framework applicable in each country, including legal definitions, criminal sanctions, and legal protection for victims. The results of the study show that there are significant differences in the handling of cyber bullying laws between countries, both in terms of the formulation of legal norms and enforcement mechanisms. This study concludes that the harmonization of cyber law policies internationally is an urgent need to create more effective and comprehensive protection for victims of digital violence, especially among adolescents and children.